Effect of the ytterbium concentration on the upconversion luminescence of Yb3+/Er3+ co-doped PbO-GeO2-Ga2O3 glasses - Bomfim, F. A.; Martinelli, J. R.; Kassab, L. R P [UNESP]; Wetter, N. U.; Neto, J. J. (Elsevier B.V., 2008)
The effect of Yb3+ concentration on the frequency upconversion (UPC) of Er3+ in PbO-GeO2-Ga2O3 glasses is reported for the first time. Samples were prepared with 0.5 wt% of Er2O3 and different concentrations of Yb2O3 (1.0-5.0 wt%). The green (523 and 545 nm) and red (657 mm) emissions are observed under 980 nm diode laser excitation. The dependence of the frequency UPC emission intensity upon the excitation power was examined and the UPC mechanisms are discussed. An interesting characteristic of these glasses is the increase of the ratio of red to green emission, through an increase of the Yb3+ concentration due to an efficient energy transfer from Yb3+ to Er3+. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Glasses; Laser spectroscopy; Luminescence; Rare-earth